2022
DOI: 10.31635/ccschem.021.202100951
|View full text |Cite
|
Sign up to set email alerts
|

Energy Pumping by Surface Collectors on Upconversion Nanoparticles for Extended Transfer and Efficient Self-Evaluable Photodynamic Therapy

Abstract: Although upconversion nanoparticle (UCNP) based luminescence resonance energy transfer (LRET) has attracted intensive attention, its application in sensing strategy for biomacromolecule detection is still limited due to the low energy transfer efficiency. Here we develop an energy pumping strategy to enhance the upconversion LRET efficiency of UCNP from 3.6% to 70.3%. Surface collector dye Cy3 is modified on UCNP surface to concentrate the scattered emission energy from interior UCNP to particle surface and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…201 Another UCNP-based self-evaluation nanoplatform for PDT was constructed by Zhang et al , and the nanoplatform consisted of QSY7-labeled DEVD peptide, photosensitizer pyropheophorbide-a (Ppa), fluorescent molecule Cy3, and UCNP. 202 The absorption and emission wavelengths of Cy3 match the UCL emission (540 nm) and QSY7 absorption, respectively.…”
Section: Cancer Stratificationmentioning
confidence: 88%
“…201 Another UCNP-based self-evaluation nanoplatform for PDT was constructed by Zhang et al , and the nanoplatform consisted of QSY7-labeled DEVD peptide, photosensitizer pyropheophorbide-a (Ppa), fluorescent molecule Cy3, and UCNP. 202 The absorption and emission wavelengths of Cy3 match the UCL emission (540 nm) and QSY7 absorption, respectively.…”
Section: Cancer Stratificationmentioning
confidence: 88%
“…Detect caspase-3 and survivin mRNA, [26] Uracil DNA glycosylases (Ung) [35] /MMP-3, [30] /MMPs [39] /MMP-3, [31] hypoxic tissues [41] Detect miR-21, [44] Zika-specific DNA in human blood serum, [45] the activity of anti-digoxigenin (Dig) antibodies, [46] intracellular target mRNA [47] /caspase-3 [48] IQ 4 587 520-706 56 000 -/--/-Eclipse 522 460-570 -/-FAM/aminoacridine Detect Guignardia citricarpa, [50] human immunodeficiency virus type 1 (HIV-1) in plasma [51] /single base pair mutations [52] TAMRA 544 470-560 85 000 FAM Detect AFB1 in beer, wine samples, [58] the mutation level of Kisten rat sarcoma (KRAS) viral gene [59] QSY7 560 500-600 92 000 Cy3/BODIPY/fluorescein (92 300; 518) Detect Cathepsin B (CaB), [67] caspase-3 [75] /E. coli outer membrane protease (OmpT) [72] /protein/ribosome conformation [76] QSY9 562 500-600 88 000…”
Section: Discussionmentioning
confidence: 99%
“…In addition, QSY molecules have been widely used as quenchers in FRET‐based fluorogenic probes in the detection of various biological events and molecules, such as guanine, [68] cysteine cathepsin (CTS), [69] cathepsin S, [70] pH, [71] E. coli outer membrane protease (OmpT), [72] β‐lactamase (BlaC), [73] bromo‐benzophenanthridinone 968 on glutaminase C (GAC), [74] caspase‐3, [75] protein/ribosome conformation, [76] liposome, [77] MMP‐2, [78] intracellular hypoxia, [79] actin, [80] myosin, [81] glucose, [82] granzyme B, [83] Botulinum Neurotoxin Serotype E, [84] and phosphatidylcholine‐specific phospholipase C [85] …”
Section: Structure–property Relationship and Application Of Quenchers...mentioning
confidence: 99%
“…Recently, Yu et al reported a lysosome-targeted and self-monitoring probe, NSLN, based on lysosome-to-nucleus immigration ( Figure 10 d) [ 72 ]. Initially, NSLN stained lysosomes in cancer cells, but immigrated into the nucleus through binding with DNA after PDT-induced apoptosis and lysosome damage.…”
Section: Pdt Evaluationmentioning
confidence: 99%